Penggunaan Media Lego Bricks Untuk Meningkatkan Kemampuan Kognitif Matematika Pada Materi Operasi Hitung Bilangan Bulat - Fida Rahmantika Hadi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to improve mathematical cognitive abilities in integer arithmetic operations through the use of lego bricks for fifth grade students of SDN 02 Winongo Madiun. This type of research is a classroom action research conducted in two cycles and each cycle is carried out twice. The research subjects were all fifth grade students totaling 17 SDN 02 Winongo Madiun. The research data were collected through observation, written tests in the form of pretest and posttest and documentation. The results of this study indicate that the Lego brick media can improve the cognitive ability of mathematics in integer arithmetic operations. This increase was marked by an increase in the number of students with test scores that exceeded the KKM, with scores between 70 and 100.With an increase in percentage of 35.5% of students who scored above the KKM, from 41.17% of students who scored in the KKM to 76, 14%. Keyword: mathematical cognitive abilities, lego bricks, integer operations